WHAT STRATEGIES WOULD BE EFFECTIVE TO HANDLE MIXED-ABILITY STUDENTS IN LEARNING ENGLISH AS A FOREIGN LANGUAGE? - Bobonazarova, Muxlisa Yomg‘ir qizi (Educational Research in Universal Sciences, 2023)
The main aim of education is not just to give students beneficial information but to teach them thinking skills, to make decisions and choices, to develop their mental abilities. Educators should stir pupils’ curiosity, creativity and imagination; broaden their horizons; deepen their way of thinking, enrich their outlook and scope of knowledge. However, every pupil has own potential. They learn or figure out something according to their character, learning style or even gender. This type of class is called mixed-ability class. The purpose of this paper is to explore teaching mixed-ability students in educational establishments.